Physiological activity of extracellular protein fraction of wheat cell culture (Experimental biology, 2019)
Antiauxin activity extracellular hydrophilic (HPL) and hydrophobic (HPB) protein fractions isolated from wheat cell suspension have been revealed. Especially HPB fraction has more antiauxin activity. revealed Cytokinine like effect of HPL protein fraction have been showed. Ability of extracellular HPB fraction to stimulate the germination of mustard seeds in stress conditions (0,5 % NaCl) have been revealed. Auxin like activity of  extracellular HPL and HPB fractions  haven’t  revealed.